Sublethal effects of a common neonicotinoid pesticide, thiamethoxam, on honey bees: impact on locomotion and thermoregulation - Tosi, Simone <1986> (Alma Mater Studiorum - Università di Bologna, 2015)
Neonicotinoids have been pointed to as a factor responsible for the increased honey bee colony losses in the last decades. Many studies have investigated the effects of the first marketed neonicotinoid, imidacloprid, while fewer have focused on thiamethoxam. One recent study showed that sublethal doses of thiamethoxam lead to colony failure by decreasing forager homing flight success. We thus decided to investigate the mechanism which caused this phenomenon. Our hypothesis was that this effect was caused by impairment of forager locomotion abilities. Therefore we tested the effects of sublethal acute and chronic exposures to thiamethoxam on forager walking (Chapter 2) and flight (Chapter 3) performances. The acute treatment (1.34 ng/bee) affected walking locomotion firstly triggering hyperactivity (30 min post-treatment) and then impairing motor functioning (60 min post-treatment). 2-day continuous exposures to thiamethoxam (32.5, 45 ppb) elicited fewer effects on walking locomotion, however both exposure modes elicited an increased positive phototaxis. Similarly, in flight experiments, the single dose (1.34 ng/bee) elicited hyperactivity shortly after intoxication (increased flight duration and distance), while longer and continuous exposures (32.5, 45 ppb) impaired forager motor functions (decreased flight duration, distance, velocity). It is known that flight muscles temperature needs to be precisely regulated by bees during flight. Therefore, we further hypothesized that the impaired flight performances of neonicotinoid intoxicated bees were caused also by thermoregulation anomalies. We tested the effects that acute thiamethoxam exposures (0.2, 1, 2 ng/bee) elicit on forager thorax temperature (Chapter 4). Foragers treated with high doses exhibited hyperthermia or hypothermia when respectively exposed to high or low environmental temperatures. In summary, we show that sublethal doses of thiamethoxam affected forager walking and flight locomotion, phototaxis and thermoregulation. We also display the intricate mode of action of thiamethoxam which triggered, at different extents, inverse sublethal effects in relation to time and dose.